A Production system study conducted at the University of the Philippines Pilot Food Plant - Deomano, Jerome Jerald; Reyes, Alfonso; del Rosario, Cecile; Saldivar-Sali, Charisse D.; Velhagen, Ramon A.; Yapjoco, Paul. (Diliman, Quezon City College of Engineering, 1991)
This study deals with the production system of the University of the Philippines Pilot Food Plant. it uses principles and concepts in Industrial Engineering to help devise improved production methods and procedures, as well as planning and control measures to assist the Food Plant in realizing its goal of increasing its production volume. It focuses on two particular product lines, and on all aspects of the production connected with these product lines. The study is also aimed at raising the Plant's level of activities with regard to the said products, in such manner as to optimize the plants capacity in terms of human, financial and technological resources.
IE 151
Feasibility study
Keywords: Philippines Pilot Food PLant; Food industry; Production engineering